HUBUNGAN PENERIMAAN DIRI PADA ORANGTUA TERHADAP KREATIVITAS INDIVIDU DENGAN ASD DENGAN MODERATOR DUKUNGAN SOSIAL PADA ORANGTUA - Adika El Nino (UNS Press, 2021)
Abstract. Everyone is born with different conditions. On such condition is that individuals are born with ASD conditions. Even with the different conditions, but individuals still have the potential that can be developed. One of these potentials is related to creativity. With the self-acceptance and perceived social support by parents, parents are expected to be able to practice parenting that is suitable for individuals with ASD to develop their potential. The study involved 34 students with autistic and parents in three districts and one municipality in the Daerah Istimewa Yogyakarta. There instruments used were the Torrance Tests of Creative Thinking-Figural, Multidimensional Scale of Perceived Social Support, and Scale of Self-acceptance. Findings from this study indicate that self-acceptance in parents can not predict of individuals with ASD. Then, the social support felt by parents can predict the creativity of individuals with ASD. In addition, social support for parents does not act as a moderator in the relationship between self-acceptance in parents and the creativity of individuals with ASD. This is not in line with previous findings.